Sistem Pendukung Keputusan untuk Menentukan Guru Terbaik dengan Metode Analytical Hierarchy Process (AHP) : Studi kasus: SDN Bergas Lor 01 - Khafid, Ahmad Noor; Mujiyono, Sri (Institut Teknologi Garut, 2025)
Teacher performance evaluation is very important in ensuring the quality of education. However, this process is often difficult because it must consider various aspects, such as personality, competence, achievement, and innovation. In this study, we developed a decision support system (DSS) using the Analytical Hierarchy Process (AHP) method to help determine the best teachers objectively. This method helps identify relevant criteria and weights in determining teacher performance evaluations. This method is capable of producing more consistent and transparent decisions. The designed system is expected to simplify the decision-making process in determining the best teachers more efficiently, thereby supporting the improvement of teacher performance.